Electric characteristics analysis on power drive system based on negative input‐resistance compensator. Issue 8 (1st August 2015) - Wang, Na; Zhou, Yuanjun; Sun, Jing; Bai, Long
Abstract : A power drive system is a typical load for the 270 V DC power distribution systems of more electric aircraft. It may cause instability of power grid, including voltage transients and current transients. A negative input‐resistance compensator with current limitation is proposed to solve the stability problem as well as to decrease both voltage transients and current transients. The main emphasis is placed on the transient characteristics research of power drive system with the proposed compensator. A dc network admittance model is established to select proper parameters for the compensator. Simulation and experiments show that the designed compensator increases system stability while satisfying the transient requirements of the power distribution system.